PENGARUH KURIKULUM MERDEKA BELAJAR TERHADAP HASIL BELAJAR EKONOMI DI MAN 1 SINTANG - Kamarullah, Heri; Marganingsih, Anna; Thoharudin, Munawar (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
The Independent Learning Curriculum is a new innovation in improving the quality of learning, giving students the opportunity to choose learning according to their interests and needs. This research investigates the impact of the Independent Learning Curriculum on economic learning outcomes at Madrasah Aliyah Negeri 1 Sintang during the 2022/2023 academic year, by considering learning motivation as a moderating factor. Data from 280 students in grades XI A to XI H were collected through questionnaires and documentation, then analyzed using path analysis. The results of the analysis show that there is a positive and significant influence of the Independent Learning Curriculum on economic learning outcomes (correlation coefficient 0.160, t value 1.822, significance 0.035), as well as a positive and significant influence on learning motivation (correlation coefficient 0.382, t value 5.908, significance 0.000). Learning motivation was also proven to have a significant effect on economic learning outcomes (correlation coefficient 0.154, t value 2.242, significance 0.016). Furthermore, the implementation of the Independent Learning Curriculum indirectly influences economic learning outcomes through the mediation of learning motivation (correlation coefficient 0.152, t value 2.042, significance 0.022).